1990
DOI: 10.1007/bf00982114
|View full text |Cite
|
Sign up to set email alerts
|

Male pheromone of swift moth,Hepialus hecta L. (Lepidoptera: Hepialidae)

Abstract: (R)-6-Ethyl-2-methyl-2,3-dihydro-4H-pyran-4-one, (1R,3S,5R)-3-ethyl-1,8-dimethyl-2,9-dioxabicyclo[3.3. 1]non-7-ene, and (1R,3S,5R)-3-ethyl-1,8-dimethyl-2,9-dioxabicyclo[3.3.1]non-7-en-6-one represent the main components in the male pheromone of the swift moth,Hepialus hecta. The amounts of the three components were 40, 5, and 5 μg per male, respectively. Structure elucidation of the compounds was based on spectroscopic data as compared to synthetic reference samples. The absolute configurations were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Among moths, benzaldehyde, benzyl alcohol, and 2-phenyl ethanol have been identified from several Noctuidae species, and danaidal (1a) and hydroxydanaidal (1b) have been found in the coremata of several Arctiidae species.While no female pheromones of Hepialidae species in Hepialoidea, a primitive group in 68 T. Ando et al Lepidoptera (see Fig. 1), have been reported, novel dihydropyrans (2a-c) and bicyclic acetals (3a-c and 4a-c) have been identified from the males of Hepialus hecta in this family [114]. Three of them, 2a, 3a, and 4a, are major components in its hindleg extract, and compounds 2c and 3b have been identified from the males of two other Hepialidae species, H. californicus [115] and Endoclita excrescens [116], respectively.…”
Section: Male Sex Pheromonesmentioning
confidence: 94%
“…Among moths, benzaldehyde, benzyl alcohol, and 2-phenyl ethanol have been identified from several Noctuidae species, and danaidal (1a) and hydroxydanaidal (1b) have been found in the coremata of several Arctiidae species.While no female pheromones of Hepialidae species in Hepialoidea, a primitive group in 68 T. Ando et al Lepidoptera (see Fig. 1), have been reported, novel dihydropyrans (2a-c) and bicyclic acetals (3a-c and 4a-c) have been identified from the males of Hepialus hecta in this family [114]. Three of them, 2a, 3a, and 4a, are major components in its hindleg extract, and compounds 2c and 3b have been identified from the males of two other Hepialidae species, H. californicus [115] and Endoclita excrescens [116], respectively.…”
Section: Male Sex Pheromonesmentioning
confidence: 94%
“…If the female seeks nectar, she has to be able to detect nectar-rich flowers. In some species, the sexual roles are reversed or changed, so that the female uses sensitive pheromone detectors to locate the male 119,186,229,231 The part of the system involving plant compound and oviposition cue detection holds true also for butterflies. With regards to sex pheromone communication, butterflies use sex pheromones only for close range attraction, so the very sensitive pheromone detection system typical of male moths is not present 25.…”
Section: Olfactory Guided Behavioursmentioning
confidence: 98%
“…α-Farnesene from plants wounded by herbivores is thought to play a role in plant defense by attracting predators and parasitoids (Van den Boom et al, 2004). In the case of Lepidoptera, α-farnesene occurs in androconial organs in males of a swift moth (Schulz et al, 1990) and Danainae butterflies (Schulz et al, 1993), and larvae of some Papilionidae butterflies secrete β-farnesene from osmeteria to defend the attacks of predatory enemies, but this is the first instance in which farnesene is part of a female moth sex pheromone. In vivo experiments with 13 C-labeled precursors revealed that β-farnesene was biosynthesized by the usual terpenoid pathway in the organ (Honda, 1990), suggesting the possibility of de novo synthesis of α-farnesene in the emerald moth.…”
Section: Discussionmentioning
confidence: 99%